THE SIGNIFICANCE OF DEMOGRAPHIC VARIABLES AND ALCOHOL CONSUMPTION IN PREDICTING EMOTIONAL EXPRESSIVITY IN ALCOHOL DEPENDENCE - Slavinskiene, Justina; Zardeckaite-Matulaitiene, Kristina (European Scientific Journal, ESJ, 2014)
The study aim: to evaluate the significance of demographic variables and alcohol consumption peculiarities in predicting emotional expressivity of alcohol-dependent patients in Lithuania. The material and method: 149 alcohol-dependent patients participated in the cross-sectional study. A self-administered questionnaire was used from the Lithuanian version of Five Expressivity Facet Scale (Gross, John, 1998), AUDIT test and demographic questions. The main results and conclusions: Alcohol-dependent patients, who perceive rehabilitation treatment demonstrate higher expressive confidence, higher positive and negative expressivity and higher impulse intensity than alcohol-dependent patients from the detoxification treatment. Alcoholdependent patients with higher level of education are more likely to demonstrate higher expressive confidence, higher the positive expressivity and higher impulse intensity. The results reveal that alcohol-dependent females have higher impulse intensity than alcohol-dependent males. Also, the results show that the consumption of champagne/wine in one evening is a significant for higher expressive confidence of alcohol-dependent people. Alcohol-dependent people who have long experience of alcohol consumption demonstrate lower positive expressivity.